Matthew Zaccaro: capstone - Zaccaro, Matthew, artist (Colorado State University. Libraries, 2022)
The artist's statement: As an artist, I work hard to create work that in its making, is an extension of myself and how I see the world. The minimalist style that I use to create elegant, easy to understand designs is a product of my many passions and how they make me feel. Fashion is one aspect of my life that has always inspired me and how I make my work. I work hard to create work that displays the beauty and status that we portray to others through fashion. Whether it be through a Nike ad design, or a clothing brand that I create, fashion is at the center of most of my work. My process has always varied for each project but I always start with the research aspect. Knowing every detail of the topic will make my ideas flow easier and give me a deeper understanding of something that I would otherwise not care for. Research is also a tool I use when I experience artist block. Researching the topic I am going to design gives me an understanding of what that topic is about and will give me ideas for aspects of design. Sketching is also part of my design process. Usually with sharpies I simply draw whatever I am thinking related to that topic and build off of those sketches. I have found that stopping the sketching process before i find an idea would correlate to my artist block.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design